Analisis Faktor yang Berhubungan dengan Ketidakpatuhan Diet pada Pasien DM Tipe 2 di Rumah Sakit Umum Royal Prima Medan - Halawa, Afeus; Gea, Niat Hati; Bestheida, Meliana (Universitas Malahayati, 2023)
ABSTRACT Diabetes is a chronic disease that cannot be cured due to the body's inability to properly process glucose into energy. The prevalence of diabetes in Indonesia in 2013 aged >15 years reached 15%, slightly lower than the prevalence in 2018 age> 15 years which is equal to 2.0%. Compliance with the treatment of people with Diabetes Mellitus is a patient's behavior in taking medication, following a diet, or following lifestyle changes. The research instrument used questionnaires and observation sheets with data collection methods through secondary data and premier data through an interview process with a sample of 30 people. The purpose of this study was to determine the analysis of factors related to dietary adherence in Diabetes Mellitus sufferers at the Royal Prima Medan General Hospital in 2023. Based on the results of the chi square test, it shows that there is an influence on the relationship of dietary noncompliance in Diabetes Mellitus sufferers with a p-value of 0.000 <0.005 so it can be interpreted that Ho is rejected. Suggestions to respondents are hoped that this research can improve dietary compliance in Diabetes Mellitus patients. Keywords: Diabetes Mellitus, Dietary compliance ABSTRAK Ketidakmampuan tubuh untuk mengubah glukosa menjadi energi dengan tepat membuat diabetes menjadi kondisi kronis yang tidak bisa disembuhkan. Di Indonesia, prevalensi diabetes pada usia 15 tahun ke atas ialah 15% saat 2013, dan 2,0% saat 2018. Tindakan pasien dalam menerima pengobatan, menjaga pola makan, atau mengadopsi kebiasaan baru yang dianjurkan sebagai bagian dari pengelolaan DM ialah ukuran ketaatan. Kuesioner dan lembar observasi merupakan alat pengumpul data primer, dilengkapi dengan data sekunder dari sumber yang ada dan wawancara dengan total 30 partisipan. Riset ini bertujuan untuk menganalisis variabel yang berkontribusi terhadap kebiasaan makan yang buruk pada individu di RSU Royal Prima Medan yang menderita DMT saat 2023. Hasil uji chi-square menampilkan bahwasanya ditemukan relasi bersignifikan antara ketidakpatuhan diet dengan diabetes mellitus. , dan p-value ialah 0,000 kurang daripada 0,005, maka begitu Ho ditolak. Diinginkan dengan memberikan saran kepada responden, riset ini dapat mengarah pada ketaatan diet yang lebih baik di antara mereka yang menderita Diabetes Mellitus. Kata Kunci: Diabetes Melitus, Kepatuhan Diet